Seasonal Variability of Phytoplankton Accessory Pigments (Chlorophyll-b and Chlorophyll-c) in the Calabar River Estuary: South Eastern Nigeria - EDDY, N.O.; EKOP, A.S.; UWANTA, E.J. (Asian Journal of Chemistry, 2010)
Seasonal variability of phytoplankton accessory pigments in the Calabar River estuary was studied during the period, July to October, which is a transition period between the rainy season and the dry season. Water samples were collected at Calcemco Jetty. The samples were analyzed for the concentration of chlorophyll-b and Chlorophyllc using spectrophotometric method. A significant positive correlation was obtained between the concentration of chlorophyll b and chlorophyll c in low tide neap (r > 0.998, n = 4, p = 0.05) and in low tide spring (r > 0.886, n = 4, p = 0.05). Correlations were also positive between the concentration of chlorophyll b and chlorophyll c in high tide neap (r > 0.75, n = 4, p = 0.05) and high tide spring (r > 0.675, n = 4, p = 0.05). The concentration at low tide during spring was significantly higher than that of high tide during neap. Apart from spring tide, when maximum values occurred in September, chlorophyll-c values attained maximum in October as found for chlorophyll-a and chlorophyll-b. There was no significant difference in concentration of chlorophyll b between high and low tide and between neap and spring tide but low tide concentrations were relatively higher than high tide concentrations. Similarly, concentrations at neap tide were relatively higher than concentrations at spring tide.